Implementation of Strategic Risk Management in Improving the Quality of Services - Saputro, Lukasiwan Eddy; Suyuthi, Nurmadhani Fitri; Muin, Sri Adrianti (Newinera Publisher, 2023)
Lukasiwan Eddy Saputro. “Implementation of Strategic Risk Management in Improving Service Quality at Ratu Aji Putri Botung Penajam Paser Utara Hospital” (Supervised by. (Nurmadhani Fitri Suyuthi and Sri Adrianti Muin). This study aims to determine the Application of Strategic Risk Management in Improving the Quality of Services of Ratu Aji Putri Botung Hospital Penajam Paser Utara. This research was conducted at Ratu Aji Putri Botung Hospital North Penajam Paser. Data collection was done through observation, interviews, and documentation. This research data was analyzed using qualitative descriptive analysis to answer the formulation of research problems. Descriptive data obtained from observations, interviews, and documentation research will be analyzed. The results of this study found and showed that the Implementation of Strategic Risk Management at Ratu Aji Putri Botung Hospital has been proven to improve the quality of health services by optimizing operational efficiency and improving patient safety. Through risk identification and mitigation, the hospital is able to reduce medical errors and resource shortages. Despite the positive impact, there is room for improvement, such as increased staff training, utilization of information technology, and active involvement of leadership in the risk management process. With these measures, the RSUD can continue to strengthen its risk monitoring and evaluation system to provide higher quality and sustainable healthcare services.